IMPLEMENTATION OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL IN SCIENCE LEARNING AT STATE E LEMENTARY SCHOOL 28 BANDAR BARU - Armansyah, Teuku; Bahri, Saiful; Saputra, Syifa (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2026)
This research aims to examine the implementation of the contextual teaching and learning (CTL) model in science subjects at SD Negeri 28 Bandar Baru and to identify supporting and inhibiting factors in the implementation of the CTL model in science subjects at SD Negeri 28 Bandar Baru. This quantitative research was conducted at SD Negeri 28 Bandar Baru. The results show that the implementation of the Contextual Teaching and Learning (CTL) learning model in science learning at SD Negeri 28 Bandar Baru has run smoothly. In the learning process, the CTL model uses 7 components: constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. The supporting factors for this CTL model include teachers as educators, student abilities, and facilities and infrastructure. At the same time, the inhibiting factors include teachers' lack of understanding of the material and lack of time.